Presenting Lily Mars - Tarkington, Booth 1869-1946; Stoll, George 1902-1985 ([Warner Bros. Entertainment, 2013)
"Musical um ein Mädchen vom Lande, das den Ehrgeiz hat, am Broadway groß herauszukommen. Als die junge Frau einen Produzenten trifft, der sie mit nach New York nimmt, sein Herz an sie verliert und zudem noch der Star einer großen Bühnenshow ausfällt, scheint sich ihr Traum zu erfüllen. [...]" [filmdienst.de]
Original: USA 1943
special features: Academy Award-winning short "Heavenly music" ; classic cartoon "Who killed who?" ; audio-only bonuses: outtake song "Paging Mr. Greenbacks, Where there's music / Broadway rhythm" ; finale alternate version, "Where there's music" finale alternate stereo version and radio show adaption with June Allyson and Van Heflin
Bildformat 1.37:1
Keywords: Film; DVD-Video